Comparison of strength between normal concrete & admixture concrete - Akoba A.S; Phulari R.C; Kembhavi S.B; N.A. Gram (Research Parks Publishing LLC, 2020)
Materials scientists, chemists, engineers, and manufacturers’ technical representatives have helped the concrete industry to improve our ability to control work times, workability, strength, and durability of Portland cement concrete by adding some supplementary substances named admixtures. The function of each admixture focuses on a specific need, and each has been developed independently of the others. Some admixtures already have chemistry that affects more than one property of concrete, and some have simply been combined for ease of addition during the batching process. To better understand recommended usage for various application of these chemicals admixture in concrete, the present study is planned to be obtained more specific information in this direction. In this investigation on performance of concrete with GGBS and different PCE based water reducing admixture the tests on compressive strength and Workability of the concrete with Ordinary Portland cement and Portland pozzolana cement with GGBS and admixture are carried out at different curing periods for M45 grade of concrete to conclude its behavior.